Interstitial lung disease associated with ALK inhibitors and risk factors: an updated comparative pharmacovigilance analysis - Dong, Junli; Li, Lulu; Deng, Tiying; Song, Haibin; Zhang, Shaohui; Zhong, Minyu (Frontiers in Pharmacology, 2024)
Background: Inhibitors of the anaplastic lymphoma kinase (ALK) gene mutation are first-line treatments in patients with ALK-positive lung cancer. FDA label warns the risk of interstitial lung disease (ILD) for patients received ALK TKIs. However, ILD associated with ALK TKIs are not fully understood. The aim of the study was to characterize the features of ALK TKIs-related ILD, and explore risk factors for ALK TKIs-related ILD. Methods: FAERS reports from 2011 quarter 1 through 2023 quarter 2 were extracted and combined. Standardized MedDRA Queries (SMQs) was used to search AEs on the preferred term (PT) level. Four algorithms were employed to quantify the signals of ILD associated with ALK TKIs. The risk of ILD was further analyzed by logistic regression. Results: A total of 20,064 reports of ALK TKIs and 640 (3.2%) reports of ILD AEs were extracted. Significant disproportionality was detected in all five ALK TKIs. Interstitial lung disease and pneumonitis were the common lung toxicity induced by ALK TKIs. Results of further analysis exhibited different spectrum of lung toxicity among various TKIs. The median onset time of ILD related to ALK TKIs was 53 days (Q1:12, Q3:209) and more than 70% of AEs occurred within first two months. Logistic regression analysis and risk prediction model both showed that different ALK TKIs and their combination with PPIs, amlodipine, magnesium oxide were independent risk factors for ILD (p＜0.05). Conclusion: ALK TKIs have different safety profiles related to lung toxicity, which normally occurred within the first two months. Combination with PPIs, amlodipine and magnesium oxide significantly increases the risk of ILD. These results provide risk prediction of ILD related to ALK TKIs and support pharmacovigilance for promoting safe prescribing in oncology.